Gingipains: Critical Factors in the Development of Aspiration Pneumonia Caused by Porphyromonas gingivalis - Benedyk, Małgorzata (J Innate Immun, 2016)
Aspiration pneumonia is a life-threatening infectious disease often caused by oral anaerobic and periodontal pathogens such as Porphyromonas gingivalis. This organism produces proteolytic enzymes, known as gingipains, which manipulate innate immune responses and promote chronic inflammation. Here, we challenged mice with P. gingivalis W83 and examined the role of gingipains in bronchopneumonia, lung abscess formation, and inflammatory responses. Although gingipains were not required for P. gingivalis colonization and survival in the lungs, they were essential for manifestation of clinical symptoms and infection-related mortality. Pathologies caused by wild-type (WT) P. gingivalis W83, including hemorrhage, necrosis, and neutrophil infiltration, were absent from lungs infected with gingipain-null isogenic strains or WT bacteria preincubated with gingipain-specific inhibitors. Damage to lung tissue correlated with systemic inflammatory responses, as manifested by elevated levels of TNF, IL-6, IL-17, and C-reactive protein. These effects were unequivocally dependent on gingipain activity. Gingipain activity was also implicated in the observed increase in IL-17 in lung tissues. Furthermore, gingipains increased platelet counts in the blood and activated platelets in the lungs. Arginine-specific gingipains made a greater contribution to P. gingivalis-related morbidity and mortality than lysine-specific gingipains. Thus, inhibition of gingipain may be a useful adjunct treatment for P. gingivalis-mediated aspiration pneumonia.